A scoring system for predicting downgrading and resolution of high‐grade infant vesicoureteral reflux. (28th June 2020) - Sjöström, Sofia; Pivodic, Aldina; Abrahamsson, Kate; Sixt, Rune; Stokland, Eira; Hansson, Sverker
Abstract: Aim: Aim of the study was to provide a scoring system for predicting downgrading and resolution of infantile high‐grade vesicoureteral reflux (VUR). Methods: Eighty‐nine infants (65 boys) with high‐grade VUR (grade 4‐5) diagnosed at median age 2.5 months and followed to 39 months had repeated investigations of VUR grade, renal damage/function and bladder function. Recurrent urinary tract infections (UTIs) were registered. Risk variables collected at 1 year were analysed as independent factors for spontaneous resolution to grades ≤2 and 0, using univariable/multivariable logistic regression. Results: A scoring system was built with a total of 14 points from four independent risk factors (sex, breakthrough UTI, type of renal damage and subnormal glomerular filtration rate). Children with persistent VUR (grade 3‐5) had higher scores compared with the group with spontaneous resolution (grade 0‐2) (mean 7.9 vs. 4.5, P  < .0001). A score of ≥8 points indicated a low probability of VUR resolution (≤14%). The model was considered excellent based on area under the ROC curve (0.82) and showed satisfactory internal validity. Conclusion: This model provides a practical tool in the management of infants born with high‐grade reflux. High scores at one year of age indicate a high risk of persistent dilated reflux.